2014
DOI: 10.1186/1471-2407-14-144
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor CAG repeats, non-random X chromosome inactivation, and loss of heterozygosity at Xq25 in relation to breast cancer risk

Abstract: BackgroundThe aim of this study was to examine the association of non-random X chromosome inactivation (XCI) and loss of heterozygosity (LOH) at Xq25 with breast cancer development.MethodsSeventy-nine breast cancer patients, 39 female lung cancer patients, 30 other cancer patients and 77 healthy females were analysed for LOH using a panel of 11 microsatellite markers spanning Xq25. The androgen receptor (AR) gene was chosen as an XCI marker.ResultsLOH of at least one microsatellite locus at Xq25 was identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Lan NH, et al (Lan et al, 2013) -OS rates at 1, 3, and 5 years following diagnosis were 0.94, 0.83 and 0.74 respectively. (Chen et al, 2014a), mitochondrial DNA content (Jiang et al, 2014), mitochondrial D-loop insertions (Tipirisetti et al, 2014), and telomere length (Qu et al, 2013). The studies included in this review identified several associations between BC risk and genes that encode apoptotic regulators (e.g.…”
Section: Vietnammentioning
confidence: 99%
“…Lan NH, et al (Lan et al, 2013) -OS rates at 1, 3, and 5 years following diagnosis were 0.94, 0.83 and 0.74 respectively. (Chen et al, 2014a), mitochondrial DNA content (Jiang et al, 2014), mitochondrial D-loop insertions (Tipirisetti et al, 2014), and telomere length (Qu et al, 2013). The studies included in this review identified several associations between BC risk and genes that encode apoptotic regulators (e.g.…”
Section: Vietnammentioning
confidence: 99%
“…And, then, re‐expression of LTF after the treatment of 5‐Aza‐Cdc told the truth that the decreased expression of LTF was, at least partially, a result of hypermethylation. However, of course, other factors, such as loss of heterozygosity ( LOH ), a high‐frequence incident in 3p21.3 region , DNA point mutations, as well as regulations of upstream genes, could not been ignored considering that 5‐Aza‐Cdc only exerted limited influence in restoring the expression of LTF . Therefore, additional efforts are necessary to be taken on elucidating the exact mechanisms of LTF inactivation in future work.…”
Section: Discussionmentioning
confidence: 99%
“…Both events, the increased longevity and the so-called "healthy ageing", which result in a smaller skewing or a greater delay in X inactivation, could be explained by the fact that, as long as the deviation process has not yet begun and the two cellular populations (Xp and Xm) remain thus in a 50:50 ratio, the compensatory effects that arise effectively counteract the expression of recessive mutant alleles [73]. On the other side of the coin, age-dependent XCI skewing can be also involved in favoring the expression of deleterious alleles, as evidenced by the late-onset of certain X-linked disorders such as Graves' disease and Hashimoto thyroiditis, scleroderma and X-linked sideroblastic anaemia, and cancer, among others [74]- [77].…”
Section: XCI Longevity and Gendermentioning
confidence: 99%